Program Pengembangan Kemandirian Ekonomi Pondok Pesantren Darul Fikri sebagai Binaan Bank Indonesia Kalimantan Barat - Gunawan; Syahbudi; Safri, Hayanuddin; Luqman (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Islamic boarding schools that implement economic independence require cooperative relationships from outside parties or government institutions in financing the needs and requirements of the Islamic boarding school unit so that it continues to run and progress, while Islamic boarding schools are synonymous with the impression of being closed. To achieve Islamic boarding school economic independence, openness and innovation are needed so that the students who graduate have ownership skills apart from the religious knowledge obtained. This research aims to describe the implementation process, impact of implementation and sustainability of the Islamic Boarding School economic independence program under the guidance of Bank Indonesia. This research uses a qualitative method with a phenomenological approach. The research is located at the Darul Fikri Islamic Boarding School. Data collection consisted of in-depth interviews, documentation and non-participant observation. The results of this research show that the assistance and guidance program from Bank Indonesia to the Darul Fikri Islamic Boarding School has been able to transform the Islamic boarding school which was once financially weak and is now financially independent and has implemented an economic independence assistance program from Bank Indonesia. Keywords: Bank Indonesia, Islamic Boarding School, Islamic Boarding School Economic Independence